PHYTOCHEMICAL INVESTIGATION AND IN VITRO ANTIDIABETIC ACTIVITY OF MELOTHRIA SCABRA - GOVINDULA, ANUSHA; Reddy, Sunayana; Manasa, Ponnam; B, Ajay kumar B (Asian Journal of Pharmaceutical Research and Development, 2019)
The family Cucurbitaceae includes a large group of crops like cucumbers, and melons which are medicinally essential. The major elements present are the phytochemicals like Terpenoids, Saponins, Tannins, Steroids, Caretenoids, Glycosides and Resins etc and the most commonly the terpenoid substance called cucurbitans. Melothria scabra belongs the family Cucurbitaceae. Melothria scabra belongs the family Cucurbitaceae. The leaves of Melothria scabra are dried and powdered. Extraction was performed by using ethanol by soxhlation method. In the present study, the phytochemical investigation and invitro anti diabetic activity was performed. It indicates the presence of Carbohydrates, Proteins, Alkaloids, Flavanoids and Glycosides. Powder analysis is performed by using dried powder. It indicates the presence of Stomata, Xylem vessels and Fibres. These extracts were screened for invitro anti diabetic activity by using the three methods: Determination of glucose adsorption capacity, Effect of plant extracts on invitro glucose diffusion, Glucose uptake by yeast cells. The plant extract has shown good increase in glucose adsorbing capacity, decrease in glucose diffusion retardation potential and significant decrease in glucose uptake thus indicating its ability to decrease the glucose availability to diffusion into blood stream.